ESTIMASI DOSIS PUPUK UNTUK BEBERAPA VARIETAS PADI DI KECAMATAN SIMELUE BARAT KABUPATEN SIMELUE - Syamsidah Djuita (Jurnal Agrista, 2003)
The objective of the research is to estimate the fertilizer dosage on rice production. This study was conducted from October to December 2002 at Simeulue Barat. Dosage of fertilizer combination would give high result for local rice variety: 135 kg ha N 144 kg ha P20s 120 kg ha K20+7 kg ha S+3000 kg ha Dolomite 15 kg PPC (u-Nutrima-L), where for rice variety: 135 kg ha N + 144 kg ha P-Os + 60 kg ha1 K,0+ 7 kg ha S 1500 kg ha Dolomite +15 kg PPC. The maximum yield of prime variety use of: 8,41 ton ha -1 and local variety is 5.64 ton ha1. This data shows that the maximum yield difference between prime variety (TR-64) and local variety was about 2,95 ton ha - 1 (54,03 %)